Comparative study of the photoluminescence performance and photocatalytic activity of CeO2/MgAl2O4 composite materials with an n-n heterojunction prepared by one-step synthesis and two-step synthesis methods. (March 2021) - Wang, Shifa; Gao, Huajing; Li, Jinyu; Wang, Yong; Chen, Chaoli; Yu, Xianlun; Tang, Shengnan; Zhao, Xinxin; Sun, Guangzhuang; Li, Dengfeng
Abstract: CeO2 /MgAl2 O4 (molar ratio 9:1) composite materials (CMAOCMs) with an n-n heterojunction were synthesized by one-step synthesis and two-step synthesis methods, and their phase purity, surface morphology, optical properties, photoluminescence properties, functional groups, and photocatalytic activity were compared. No matter which method is used to synthesize the CMAOCMs, the host lattice is CeO2 with a cubic phase. The mean particle size of the CMAOCMs prepared by the one-step synthesis and two-step synthesis methods is 90 and 50 nm, respectively. The CMAOCM prepared by the one-step synthesis method exhibits good photoluminescence properties because of the high recombination rate of electron-hole pairs. A dye concentration of 5 mg/L, a catalyst content of 1 g/L, and pH 13 were selected for photocatalytic degradation of the dye methylene blue by the CMAOCM photocatalyst. The CMAOCM prepared by the two-step synthesis method exhibits high photocatalytic activity for the degradation of methylene blue because of the synergistic effects of phase purity, specific surface area, light absorption capacity, and charge transfer and separation efficiency. Highlights: One-step synthesis and two-step synthesis methods were used to synthesize CeO2 /MgAl2 O4 (molar ratio 9:1) composite materials. The photoluminescence properties and photocatalytic activity of the CeO2 /MgAl2 O4 composite materials were compared. A possible photocatalytic mechanism of the CeO2 /MgAl2 O4 composite materials is proposed.